Pendekatan Organizational Learning dalam Implementasi Kurikulum Merdeka yang Mengintegrasikan Pembelajaran Berdiferensiasi di Sekolah Swasta Kabupaten Semarang: Organizational Learning Approach in Implementing Independent Curriculum Integrating Differentiated Learning in Private Schools in Semarang Regency - Trimurtini, Trimurtini; Mulyani, Petra Kristi; Nugraheni, Nursiwi; Wulandari, Desi; Sari, Elok Fariha (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The problem faced by private schools is that teachers' ability to plan and differentiate learning is not optimal. The purpose of this community service activity is to optimize the role of teachers in designing initial assessments as a support for differentiated learning planning to serve students' learning needs in the classroom. The solution offered to solve partner problems is socialization and assistance in compiling initial assessments as a basis for creating differentiated learning; differentiated learning assistance. The four stages of implementing this community service activity include adopting organizational learning (OL). The four main stages are socializing, externalizing, combining, and internalizing. This community service activity involved three students. The results of the community service activities carried out in May-September 2024 exceeded the target output, which showed that teachers' knowledge of differentiated learning after socialization reached an average of 81.06 and was categorized as good at 69.7%. The FGD results showed that the implementation of the activities showed that the principal and teachers could prepare, implement, or support differentiated learning well.